Investigate the Technology of Preparing High-dynamic Range Images for Hosting on Websites - Ярослав Володимирович Зоренко (Технологія і техніка друкарства, 2018)
This work investigate the problem of the process of preparing high-dynamic range images (HDR-image) for hosting on websites. The proper functioning of websites it is necessary to take into account the effect of the large volume of HDR-image information. Therefore, the result of present research work will allow to determine the rational values of visual quality and file size of digital images, as well as to enhance the functionality of websites with HDR-image.